Training on Preparing Conventional and Digital Financial Records for Community Groups in Tebon Village, West District, Magetan Regency, East Java Province - Rahmawati Sururama; Daffa Syadad Felix; Lion Luthfi Berliansyah (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2025)
Lack of knowledge regarding financial recording is a particular obstacle for the Community Group (POKMAS) of Tebon Village, especially in managing trader contributions. Sometimes financial reporting is only done verbally without any evidence through financial records or in a makeshift manner. This results in losses for traders due to double billing, and the POKMAS itself often covers up the shortfall in these contributions. Therefore, the purpose of this activity is to train POKMAS members in preparing financial records conventionally, namely by creating financial administration books, and digitally, namely through the RT PINTAR application, to assist POKMAS in recording and reporting trader contribution management. The method used consists of three stages: Pre-implementation, Implementation, and Evaluation. The results obtained from this activity were 12 participants (86%) of 14 participants who concluded that this activity was effective and efficient in supporting their activities, especially in managing trade contributions. However, there were 2 participants (14%) who were unable to follow it properly, especially in digital financial recording due to age factors. Overall, this training activity, both conventional and digital, had a positive impact on the community and is expected to be widely implemented.